2016
DOI: 10.1007/s00127-016-1312-6
|View full text |Cite
|
Sign up to set email alerts
|

Is employment status in adults over 25 years old associated with nonmedical prescription opioid and stimulant use?

Abstract: Purpose Nonmedical use of prescription opioid and stimulants (NMUPO and NMUPS, respectively) has declined in recent years, but remains an important public health problem. Evidence regarding their relationships with employment status remains unclear. We determined the relationship between employment status and NMUPO and NMUPS. Methods We analyzed a cross-sectional, nationally representative, weighted sample of 58,486 adults, ages 26 years and older, using combined 2011–2013 data from the National Survey on Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Our results showed a negative association between unemployment rates and substance abuse admissions for stimulants; however, the relationship was altered during economic recessions. In prior research, being unemployed or working part-time was associated with increased use of stimulants [ 30 ]. A possible explanation for this discrepancy is the perception of stimulants compared to other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed a negative association between unemployment rates and substance abuse admissions for stimulants; however, the relationship was altered during economic recessions. In prior research, being unemployed or working part-time was associated with increased use of stimulants [ 30 ]. A possible explanation for this discrepancy is the perception of stimulants compared to other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A National Survey on Drug Use and Health (NSDUH) conducted in the US reported that about half (55.1%) of the adults with the substance use disorder were employed full time [ 39 ] which supports our observation ( Table 1 ). Finding from a national survey conducted by Perlmutter and Colleagues [ 40 ] indicated that the correlates of prescription drug use with job status vary within the different classes of prescription drugs; those who are unemployed had higher odds of using prescription opioid whilst non-full time employment showed higher odds of using prescriptions stimulants. The role of the type of occupational classes in PD misuse is thus of utmost importance to understand the mode of access to these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…148 They found that the overall past year prevalence of NMUPO and NMUPS were 3.48 and 0.72%, respectively; among those unemployed, the prevalence of NMUPO and NMUPS were the highest of the four employment groups, at 6.91 and 7.01%, respectively. 148 were the highest for adolescents who either: 1) reported the medical use of prescription opioids after initiating NMUPO or 2) reported only NMUPO. 149 Furthermore, adolescents in these two groups had significantly higher odds of alcohol use disorder (AUD), cannabis use disorder (CUD), and the other drug use disorders (ODUD) compared to adolescents who had no history of medical or nonmedical use of prescription opioids (refer to Table 2.3 for all adjusted odds ratios).…”
Section: Prescription Stimulantsmentioning
confidence: 97%
“…146 Another recent study published by Perlmutter et al investigated whether employment status was associated with NMUPO and nonmedical use of prescription stimulants (NMUPS). 148 The study included adults aged 26 and older who participated in the 2011 to 2013 NSDUH and examined covariates that related to their employment status (i.e., employed full-time, employed part-time, unemployed, and not in the workforce) and past year NMUPO and NMUPS use. 148 They found that the overall past year prevalence of NMUPO and NMUPS were 3.48 and 0.72%, respectively; among those unemployed, the prevalence of NMUPO and NMUPS were the highest of the four employment groups, at 6.91 and 7.01%, respectively.…”
Section: Prescription Stimulantsmentioning
confidence: 99%
See 1 more Smart Citation